Effect of inoculation with strains of Rhizobium and nitrogen levels on qualitative and quantitative characteristics and nitrogen of white bean varieties under climatic conditions of Markazi province - Masoud Dadivar; Mohammad Ali Khodshenas; Javad Ghadbeyklou (پژوهش‌های حبوبات ایران)
Introduction Legumes, such as common beans (Phaseolus vulgaris L.) have the ability to form a symbiotic relationship with soil bacteria capable of trapping nitrogen gas (N2) from the atmosphere and converting it into ammonia, which can be used by the plant for growth, development and seed production. The capacity of legumes to fix atmospheric nitrogen gives them an advantage over non-leguminous crops when grown on soils low in nitrogen. In many region of the world where common beans are grown, nitrogen fixation is limited by unfavorable soil conditions, temperature and water stress. Despite the numerous factors that comprise nodulation and nitrogen fixation, legumes generally assimilate 50% to 70% of their nitrogen via symbiotic nitrogen fixation. However, relative to other legumes, the common beans (Phaseolus vulgaris L.) are poor nitrogen fixers. The role of biological fertilizers is important in improvement of organic farming. Rhizobium is an economically and environmentally friendly microorganism that is used as biofertilizer. Because the Markazi province is one of the most important areas for bean cultivation in the country, therefore understanding the appropriate rhizobium strains with white bean varieties recommended for cultivation in the region is important.